PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING TERHADAP LITERASI BACA TULIS SISWA V SD NEGERI 047159 KETAREN KABUPATEN KARO - Sidebang, Restio; Karo, Karmila Br; Sarumaha, Rizal Susanto (Universitas Quality, 2025)
This study aims to determine the effect of using the Student and Explaining model on students' reading and writing literacy in grade V students of SD Negeri 047159 Ketaren, Karo Regency. The research method is quantitative. The type of research applied is quasi-experimental (one group pretest posttest design). The research sample was grade V students of SD Negeri 047159 Ketaren, Karo Regency. Based on the results of the study in the experimental class, classical completeness was obtained on the posttest from 24 students for learning outcomes reaching 21 students (87.5%) completed classically and 3 students had not completed from grade V students of SD Negeri 047159 Ketaren, Karo Regency. Based on the calculation of the experimental class t-test statistics, there was a significant influence in the use of the Student and Explaining model on students' reading and writing literacy in grade V students of SD Negeri 047159 Ketaren, Karo Regency. Based on the results of the study, the researcher found that there was a significant influence with the results, so t0.05 = 2.06 was obtained. After obtaining t count = 7.06 and t table = 2.06, then obtained t count and t table or 7.06 and 2.06. The conclusion of the study, the hypothesis can be accepted, it can be said that the Student Facilitator And Explaining model has a significant effect on the Reading and Writing Literacy of class V students of SD Negeri 047159 Ketaren, Karo Regency, 2024/2025 Academic Year.